Elastic laboratory measurements and modeling of saturated basalts. Issue 3 (12th March 2013) - Adam, Ludmila; Otheim, Thomas
Abstract: [1] Understanding the elastic behavior of basalt is important to seismically monitor volcanoes, subsea basalts, and carbon sequestration in basalt. We estimate the elastic properties of basalt samples from the Snake River Plain, Idaho, at ultrasonic (0.8 MHz) and seismic (2–300 Hz) frequencies. To test the sensitivity of seismic waves to the fluid content in the pore structure, measurements are performed at three saturation conditions: saturated with liquid CO2, water, and dry. When CO2 replaces water, the P‐wave velocity drops, on average, by 10%. Vesicles and cracks, observed in the rock microstructure, control the relaxation of pore‐fluid pressures in the rock as a wave propagates. The bulk and shear moduli of basalts saturated with liquid CO2 are not frequency dependent, suggesting that fluid pore pressures are in equilibrium between 2 Hz and 0.8 MHz. However, when samples are water saturated, the bulk modulus of the rock is frequency dependent. Modeling with Gassmann's equations predicts the measured saturated rock bulk modulus for all fluids for frequencies below 20 Hz but underpredicts the water‐saturated basalt bulk modulus for frequencies greater than 20 Hz. The most likely reason is that the pore‐fluid pressures are unrelaxed. Instead, the ultrasonic frequency rock moduli are modeled with high‐frequency elastic theories of squirt flow and Kuster–Toksöz (KT). Although KT's model is based on idealized pore shapes, a combination of spheres (vesicles) and penny‐shaped cracks (fractures) interpreted and quantified from petrographical data predicts the ultrasonic dry and saturated rock moduli for the measured basalts. Key Points: Monitoring the replacement of water by CO2 over time with seismic is possible Gassmann and Kuster‐Toksoz models predict measured rock elasticity Cracks in water‐saturated basalt result in a frequency dependent bulk modulus